JURIDICAL REVIEW OF PARKING MANAGEMENT ACCORDING TO REGIONAL REGULATION NUMBER 17 OF 2006 ON THE MANAGEMENT OF ON-STREET PARKING IN THE MAKASSAR CITY AREA - Labbase, Mudhiah Fadhilah; Kasmawati, Andi; Agus, Andi Aco (Jurnal Aktor, 2025)
This study aims to: (1) Review the management policy of public roadside parking based on Regional Regulation (Perda) Number 17 of 2006. (2) Identify obstacles in the management of public roadside parking in Makassar City. This study uses a qualitative approach and a qualitative descriptive research type. Data collection techniques through observation, interviews, and documentation. From the results of the data obtained and analyzed through data reduction, data presentation, and drawing conclusions. The research results show that: (1) Management of public roadside parking in Makassar City is regulated through Regional Regulation Number 17 of 2006 which covers the following aspects: a) planning by Perumda Parkir Makassar Raya which includes parking spot arrangement, tariff setting, and parking attendant management. b) Policy implementation has not been effective because there is still a gap between the rules and practices in the field. c) Supervision and evaluation are carried out through an integrated monitoring system and a quick response to reports from parking attendants or users in order to create better service. Thus, the parking management policy already has a legal basis and a structured implementation system, but the effectiveness of its implementation in the field still needs to be improved. (2) Obstacles to managing public roadside parking in Makassar City include a lack of human resources, inadequate facilities and infrastructure, and a lack of public awareness and compliance. The prevalence of unofficial parking attendants and weak law enforcement and oversight by local governments are key factors hindering effective parking management. This has led to low public satisfaction with parking services and reduced local revenue.